First Report of Apium virus Y on Cilantro, Celery, and Parsley in California - Tian, T (Plant disease, 2008)
Recently, Apium virus Y (ApVY) was detected in field-grown cilantro (Coriandrum sativum), celery (Apium graveolens), and parsley (Petroselinum crispum) in California. In 2003, cilantro plants growing in three different fields in California (Monterey, San Joaquin, and San Luis Obispo counties) expressed symptoms of mosaic, vein clearing, and stunting. When plant sap was examined by transmission electron microscopy, flexuous, rod-shaped virus particles were observed. Total RNA was extracted from the symptomatic cilantro plants and used as a template in reverse transcription (RT)-PCR using universal potyvirus primers according to Chen et al. (1). The RT-PCR product was cloned into pGEM-T (Promega, Madison, WI) and the insert of 1,713 bp was sequenced (GenBank Accession No. EU515125). Nucleotide sequences from clones derived from three different infected cilantro plants were 89 to 97% identical to ApVY sequences encoding partial sequence of polyprotein in GenBank (Accession Nos. AY049716, EU127499, AF207594, AF203529, and EU255632). In 2007, celery plants showing necrotic line patterns and necrotic lesions on lower leaves and petioles were observed in several fields in two coastal counties in California (Monterey and Santa Clara counties). Flexuous, rod-shaped virus particles were also observed in the sap of those plants. ELISA for Cucumber mosaic virus and RT-PCR for Celery mosaic virus were negative. ApVY specific primers were designed on the basis of a consensus sequence of ApVY identified from cilantro in 2003; reverse primer 5'-GGCTCTTGCTATAGACAAATAGT-3' and forward primer 5'-GAAGACCAAGCCAATGTGTGTA-3'. The sequence of RT-PCR products (GenBank Accession No. EU515126) amplified from infected celery had 90 to 98% nucleotide identity to ApVY. When the deduced amino acid sequences of NIb and CP regions from both cilantro and celery were used for comparison, they showed 95 to 99% identity with the known ApVY GenBank sequences mentioned above. More than 10 asymptomatic parsley plants growing in fields adjacent to the infected celery were also tested for ApVY and found to be infected. ApVY was previously identified in three Apiaceae weeds in Australia (2) and in celery in New Zealand (3). To our knowledge, this is the first report of ApVY on cilantro, celery, and parsley in California. References: (1) J. Chen et al. Arch. Virol. 146:757, 2001. (2) J. Moran et al. Arch. Virol. 147:1855, 2002. (3) J. Tang et al. Plant Dis. 91:1682, 2007